A TERTIARY PERSPECTIVE OF THE SUGARCANE-BASED AGRO-INDUSTRY SUSTAINABILITY ANALYSIS - Rohayati; Marimin; Hardjomidjojo, Hartrisari; Fahma, Farah; Putranto, Kartiko Eko (Jurnal Teknologi Industri Pertanian, 2024)
Sustainability has given significant consideration to the development of the agricultural sector, particularly the sugarcane-based agro-industry. Extensive research on sustainability analysis has been explored across different fields, including the sugarcane-based agro-industry. A wide range of primary studies has focused on diverse aspects of sustainability. Various secondary studies, such as systematic reviews and mapping studies, have also been documented. Nonetheless, performing tertiary research in this critical domain remains essential to systematically identify, evaluate, and categorize these secondary studies. This tertiary study utilized the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework for a systematic literature review, focusing on sustainability analysis within the agricultural sector, particularly the sugarcane-based agro-industry. A search protocol was applied for article identification, followed by articles’ screening and selection. Content analysis was conducted using Biblioshiny in RStudio, followed by a descriptive analysis. A total of 27 secondary studies were reviewed to gain deeper insights into the evolution of the research topic productions, as well as key trends. This study also acknowledges its limitations and provides key recommendations for future research in the field, which were considered in the results. Keywords: Biblioshiny, sugarcane-based agro-industry, sustainability analysis, systematic review, tertiary study